Empathy, Sense of Power, and Personality: Do They Change During Pediatric Residency?. Issue 8 (August 2015) - Greenberg, Larrie; Agrawal, Dewesh; Toto, Regina; Blatt, Benjamin
Abstract : Objectives: Empathy is a critical competency in medicine. Prior studies demonstrate a longitudinal decrease in empathy during residency; however, they have not included pediatric residents. The relations among the expression of empathy, sense of power (ability to influence other's behavior), and personality traits in residents also have not been addressed. Lastly, there are no data on how residents compare with the general nonmedical population in their expression of empathy. The purposes of our study were to assess whether empathy, sense of power, and personality type were statistically correlated; if resident empathy declines over time; and how resident empathy compares with that of nonmedical peers. Methods: In 2010, a cohort of individuals entering pediatric residency were given three validated survey instruments at the beginning of their first and third years of training to explore longitudinal changes in empathy, sense of power, and major personality traits. Results: We found no decrease in resident empathy in 2 years of pediatric training, no changes in their sense of power, and no statistically significant correlation between empathetic tendencies and sense of power. When compared with the general nonmedical population, pediatric residents rated themselves higher in empathy. As expected, the two components of empathy (empathic concern and perspective taking) were moderately correlated. Of the major personality traits, only agreeableness showed significant correlation with empathy. Conclusions: Pediatric resident empathy did not decrease longitudinally, unlike studies in other residents. There was no inverse relation between self-perceptions of sense of power and empathy as is present in the business literature. Finally, pediatric resident empathy was significantly higher when compared with a general nonmedical population. Abstract : Empathy is a critical competency in medicine. The authors assess whether empathy, sense of power, and personality type were statistically correlated; whether resident empathy declines over time; and how resident empathy compares with that of nonmedical peers.